Bonding, Structure, and Stability of [(Na)n(Phe)m]n+ Clusters: Some Surprising Results from an Experimental and Theoretical Investigation in Gas Phase. (7th March 2013) - Caetano, Melissa S.; Ramalho, Teodorico C.; Vieira, Tales G.; Gonçalves, Arlan da Silva; Mancini, Daiana T.; da Cunha, Elaine F. F.
Abstract : Structure and stability of [ ( N a ) n ( P h e ) m ] n + clusters in the ground state were analyzed at the theoretical and experimental levels. Our experimental and theoretical findings showed that the [ ( N a ) n ( P h e ) m ] n + clusters in gas phase tend to form mainly planar rings of four members. The symmetry and the small dipole moment in these specific configurations suggested that their stability could be associated with an alignment of the water molecules, maximizing attractive electrostatic interactions caused by changes in the charge distribution of the clusters.